INTERPRETIVE STRUCTURAL MODELING OF ANTECEDENTS AFFECTING EMPLOYEE ENGAGEMENT AND BUSINESS PERFORMANCE IN HOTEL INDUSTRY - อิ่มเอิบ เมทยา; แสนชัยธร กฤตพา; นัยพินิจ อารีย์; รุ่งเรือง พลิศา (RMUTT Global Business and Economics Review, 2019)
The study aimed to examine the relationships between antecedents and consequences of employee engagement in hotel industry. Five experts were interviewed to gather insights for creating contextual relationships between these variables. The findings from interpretive structural modeling indicated high interrelationship and interconnectivity results show compensation and benefits affect to knowledge storage and retrieval and organizational citizenship behavior. Additionally, MICMAC analysis results signified that employee engagement and its antecedents and consequences were classified as linkage drivers.